Wireless battery free fully implantable multimodal recording and neuromodulation tools for songbirds - Ausra, Jokubas; Munger, Stephanie J.; Azami, Amirhossein; Burton, Alex; Peralta, Roberto; Miller, Julie E.; Gutruf, Philipp (Nature communications, 2021)
Wireless battery free and fully implantable tools for the interrogation of the central and peripheral nervous system have quantitatively expanded the capabilities to study mechanistic and circuit level behavior in freely moving rodents. The light weight and small footprint of such devices enables full subdermal implantation that results in the capability to perform studies with minimal impact on subject behavior and yields broad application in a range of experimental paradigms. While these advantages have been successfully proven in rodents that move predominantly in 2D, the full potential of a wireless and battery free device can be harnessed with flying species, where interrogation with tethered devices is very difficult or impossible. Here we report on a wireless, battery free and multimodal platform that enables optogenetic stimulation and physiological temperature recording in a highly miniaturized form factor for use in songbirds. The systems are enabled by behavior guided primary antenna design and advanced energy management to ensure stable optogenetic stimulation and thermography throughout 3D experimental arenas. Collectively, these design approaches quantitatively expand the use of wireless subdermally implantable neuromodulation and sensing tools to species previously excluded from in vivo real time experiments. Studies requiring neural modulation in species that fly are difficult because of the need for wired connections to record experimental data. Here, Ausra et al. present a wireless and battery free device that achieves this in songbirds, model organisms used to study vocal learning and maintenance.